Pengembangan Model Bimbingan Online untuk Meningkatkan Social Presence Mahasiswa Pendidikan Jarak Jauh - Isriyah, Mudafiatun; Awlawi, Addahri Hafidz; Degeng, I Nyoman S; Muslihati, Muslihati (Jurnal Bimbingan dan Konseling Terapan, 2023)
The purpose of this study:to develop, validate an online tutoring model based on ADDIE model to improve social presence of Distance Education (DE) students, help tutors reconstruct knowledge, experience more strategically, for tutors can design and implement more structured. This is a developmental study divided into 5 phases: existing methods and DE strategy review, DE model development, Delphi round 1, Delphi round 2, model validation. After reviewing relevant literature and existing strategies in phase 1, the first step of creating a DE model was created in phase 2, followed by phase 3 and phase 4, two rounds of Delphi conducted by experts, reviewing the final version of the manual and syntax model (SM) created and validating in phase 5. With respect to each ADDIE phase, the online guidance model outlines: representative points, structured activities, support strategies. both Online Social Presence Guidance (OSPG) and SM models, in order to more clearly identify the entire process. Finally, this research provides some recommendations for tutors and practitioners in choosing an online guidance model, according to the previous needs analysis, training tutors, training students, then researching to find effective guidance, techniques and media openly to change. This research recognizes its excellence by evoking and considering psychological factors, due to time constraints, this research needs to be carried out further.